Evaluasi Usability Sistem Informasi Akademik Mahasiswa untuk Orang Tua Mahasiswa Universitas Brawijaya - Argandarining Ilmi Harnis; Hanifah Muslimah Az-Zahra; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Sistem Informasi Akademik Mahasiswa Universitas Brawijaya (SIAM UB) is a system designed for informing students' academic achievement during their study. SIAM UB allows parents to access their children's academic achievement and gives transparation of students' academic information for both parents and university. The study aims to find problems faced by its users when interacting with SIAM UB then refine its interface to improve its ease access utilizing Usability Testing method and Interview by dividing 3 user types based on their habit in using the information technology. To measure accelerate use efficiency, then to measure succes task use effectiveness and to measure satisfaction use System Usability Scale quesioner. According to the preliminary study conducted, there are 6 problems found: less appropriate font size, menu setting, buttons in the form of text link or icon, scrolling needs, rigid interface, and graph-less. The refinings conducted are enlarging the font size, grouping the menus and submenus, eliminating the black block on the table, changing students' information position to reduce scrolling used, and adding graph on the home. The refining result shows that: 1) the effectiveness value increases by 93% to 100%; 2) the access time increases by 233 seconds to 173 seconds; 3) the satisfaction scale with the SUS questionnaire increases from 56.5 to 72.5.